1985
DOI: 10.1190/1.1486944
|View full text |Cite
|
Sign up to set email alerts
|

Reply by the author to M. J. Hall

Abstract: The definitive article “Airborne gravity is here!,” as well as my responses to published “Discussions” of it, were consciously directed to all readers of Geophysics. After 55 years of associations with geologists, geophysicists, exploration managers, university students, and editors (with more than 50 publications), I believe that I may have some competence to judge this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 0 publications
1
16
0
1
Order By: Relevance
“…Parthenogens would seem to be more likely to inhabit islands (Cuellar, 1977) due to their colonization potential, and perhaps a third of the taxa recorded from South Pacific islands are known or suspected parthenogens (data from Hammer, 1982). Most of these belong to the Desmonomata or Lohmanniidae.…”
Section: Geographical Distributionmentioning
confidence: 96%
“…Parthenogens would seem to be more likely to inhabit islands (Cuellar, 1977) due to their colonization potential, and perhaps a third of the taxa recorded from South Pacific islands are known or suspected parthenogens (data from Hammer, 1982). Most of these belong to the Desmonomata or Lohmanniidae.…”
Section: Geographical Distributionmentioning
confidence: 96%
“…In the conventional way, the wastewater is treated through different stages starting from primary treatment to advanced (tertiary) treatment. The advanced treatment is designed mainly to remove the nitrogen and the phosphorus to control eutrophication [18]. Compared to the standards (Chloride 1000, Sulfate 2000, Alkali carbonates and bicarbonates 1000, and Total dissolved solids 2000 mg/L), the characteristics of the recycled water used in this study were found to be acceptable by the masonry blocks standards authority in Dubai [1].…”
Section: Recycled Wastewatermentioning
confidence: 88%
“…For example, the membrane filters (reverse osmosis (RO), micro, ultra, and Nano-filtration) are widely used to remove the dissolved solids (DS) and particulate matter (PM); the membrane bioreactor (MBR) systems are increasingly used now as an efficient technique to reclaim wastewater; the oxidation technique which is advanced to combine ozone, ultraviolet (UV) light, and hydrogen peroxide to create the highly reactive hydroxyl radical (.OH) [4]. The use and level of treatment required, dictates the cost of water recycling [4], [13]- [17].…”
Section: Astesj Issn: 2415-6698mentioning
confidence: 99%